Keselarasan Prinsip-Prinsip Siyasah Dusturiyah dengan Otonomi Daerah di Indonesia - Najwa Fakhira Hisbuddin; Nurul Alfatihah Rahman; Kurniati K (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Regional autonomy from the perspective of Islamic constitutional law is the delegation of authority from the head of state to the governor or regional head to regulate and manage their territory for the benefit of the people, known as Al-Imarah Al-Khashshah. This study aims to determine how the concept of regional autonomy is understood from the perspective of Islamic constitutional law. The research method used is a qualitative approach with document analysis aimed at gaining a deep understanding of regional autonomy from the perspective of Islamic constitutional law. The results of the study indicate that although there are challenges, such as differences in the sources of legitimacy of power, it is substantially in line with the principle of siyasah dusturiyah in order to realize public welfare.